Research methodology in extension education - Dileep Kumar Dangi; K S Kadian; Moti Lal Meena (New Delhi : Satish Serial Publishing House, 2016)
This book is written as a reference book to full fill the demand of such book for the students and faculty of the postgraduate and doctorate students. It covers all most all topics of research methodology needed for NET/JRF/SRF/ARS and entrance examinations of IARI and NDRI etc. competitions. It is a useful hand book for the students and teachers of the social science faculty. About 800 multiple choice questions related to research methodology are given in this book to provide a question bank for the readers, in last chapter glossary is given to provide quick review of the terminology related to research methodology in social sciences. Other chapters like measurement, research designs, methods of data collection, sampling methods, types of research designs and parametric and non-parametric statics are given in detail to make it a complete book for research methodology. All the complex material is presented in lucid form to make the book easy to grasp for students.
This book is written as a reference book to full fill the demand of such book for the students and faculty of the postgraduate and doctorate students. It covers all most all topics of research methodology needed for NET/JRF/SRF/ARS and entrance examinations of IARI and NDRI etc. competitions. It is a useful hand book for the students and teachers of the social science faculty. About 800 multiple choice questions related to research methodology are given in this book to provide a question bank for the readers, in last chapter glossary is given to provide quick review of the terminology related to research methodology in social sciences. Other chapters like measurement, research designs, methods of data collection, sampling methods, types of research designs and parametric and non-parametric statics are given in detail to make it a complete book for research methodology. All the complex material is presented in lucid form to make the book easy to grasp for students.
Keywords: Research methodology for social sciences; NET/JRF/SRF/ARS exam preparation; Multiple choice questions; Research design and methods; Glossary of research terms; Lucid explanation of complex concepts